МОДЕЛИРОВАНИЕ ВЫХОДНОГО НАПРЯЖЕНИЯ МНОГОУРОВНЕВОГО ИНВЕРТОРА С ПРОСТРАНСТВЕННО-ВЕКТОРНОЙ МОДУЛЯЦИЕЙ ДВУХ ЛИНЕЙНЫХ НАПРЯЖЕНИЙ - Лопаткин, Н.Н. (Інститут електродинаміки НАН України, Київ, 2016)
One of the implementation variants of the algorithm of the space vector pulse-width modulation of the two delta voltages of the multilevel autonomous voltage source inverter, using the five-segment sequence of the three vectors switching is offered. The diagrams of the dependences of the output voltage THD and integral factors of harmonics on the amplitude modulation index are obtained for the various values of the frequency modulation index as a result of Mathcad simulation. References 4, figures 5.